From ‘Homer’s Synonymy (adjectives χρv́σεος and ξανθός) - Malinauskienė, Nadežda (Kalbotyra, 1987)
Comparative analysis of two adjectives - χρv́σεος “golden” ξανθός “fair-haired” in Homer’s poetry leads us to tile conclusion that the adjective χρv́σεος as frequently occurring in the poems characterised by its more complex semantic structure and, due to its freer usage, can be applied to a greater quantity of words than the adjective ξανθός.On the other hand, the adjective ξανθός in Homer’s poems can be characterised as possessing a limited range of usage however, denoting different shades of fair hair in human beings and horses, it embraces a wider range of colour than the adjective χρv́σεος does. Besides, as a result of its loss of etymological links, the adjective ξανθός does not indicate any reference to concrete objects (compare: “golden” and “sold”). All this permits the said adjective to become a most general and abstract denomination of the yellow colour in the language of later authors, where the adjective ξανθός has come into free usage.